2021
DOI: 10.1515/hsz-2021-0173
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the modulation of PDGF/PDGFR-β complexation by hyaluronan derivatives

Abstract: Angiogenesis is an important physiological process playing a crucial role in wound healing and cancer progression. Vascular endothelial growth factor (VEGF) and platelet derived growth factor (PDGF) are key players in angiogenesis. Based on previous findings regarding the modulation of VEGF activity by glycosaminoglycans (GAG), here we explore the interaction of hyaluronan (HA)-based GAG with PDGF and its receptor PDGFR-β by applying molecular modeling and dynamics simulations in combination with surface plasm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…An increase in the expression of PDGFRβ was seen in multiple tumors, including gastrointestinal tumor, lung cancer, breast cancer, hepatocellular carcinoma, and pancreatic cancer 31 . Moreover, PDGFRβ signaling was identified to facilitate cell proliferation, metastasis, and angiogenesis of tumors by activating PI3K/AKT and Ras/MAPK pathways 32 . Our results found PDGFβ stimulation in ccRCC cells led to an increase in glycolysis, lactate production, as well as histone lactylation, which in turn activated PDGFRβ transcription, thereby forming a vicious cycle that further accelerates the progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the expression of PDGFRβ was seen in multiple tumors, including gastrointestinal tumor, lung cancer, breast cancer, hepatocellular carcinoma, and pancreatic cancer 31 . Moreover, PDGFRβ signaling was identified to facilitate cell proliferation, metastasis, and angiogenesis of tumors by activating PI3K/AKT and Ras/MAPK pathways 32 . Our results found PDGFβ stimulation in ccRCC cells led to an increase in glycolysis, lactate production, as well as histone lactylation, which in turn activated PDGFRβ transcription, thereby forming a vicious cycle that further accelerates the progression of ccRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis also revealed that the DBM contains many components that regulate cell behavior and function. For example, fibronectin and laminin (LAMC1 and LAMB2) are used to increase cell adhesion, 26 PDGFR-β plays an important role in the process of early hematopoiesis and blood vessel formation, 41 and PGs facilitate the binding of growth factors, ensuring good cell adhesion, migration, growth, and proliferation. 25,42 Biomaterials possess mechanical properties similar to original tissues, which not only provide a biomimetic mechanical environment to mediate biological behavior and function during tissue regeneration, but are also helpful for preventing contraction, expansion, or stretching during reconstruction.…”
Section: Paper Biomaterials Sciencementioning
confidence: 99%
“…Sulfated hyaluronan was shown to have a clear binding pose in its complex with the TGF-β1/TβR-I/TβR-II complex that is energetically favorable and electrostatically driven, in contrast to non-sulfated hyaluronan, and a particular lysine residue in TβR-I is key to interactions with sulfated hyaluronan carboxylate and sulfate functional groups [ 158 ]. Similarly, non-sulfated hyaluronan oligosaccharide barely interacts with the complex of PDGF and its receptor PDGFR-β, whereas chemical sulfation of hyaluronan substantially increases its binding [ 159 ]. While directly getting estimates of binding free energies from standard atomic-resolution explicit-solvent molecular dynamics simulation is a difficult task, it is relatively easy to do so by applying a continuum solvent approximation to snapshots taken from explicit-solvent molecular dynamics trajectories using the molecular mechanics Poisson-Boltzman surface area (MM-PBSA) or molecular mechanics generalized Born surface area (MM-GBSA) methods [ 160 , 161 , 162 , 163 ], and these methods are useful tools in the context of glycosaminoglycan–protein binding [ 164 ], including as applied to the hyaluronan–cytokine complexes above.…”
Section: Atomic-resolution Molecular Dynamics Simulations Of Hyaluron...mentioning
confidence: 99%